2020
DOI: 10.1021/acs.joc.9b03513
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl-Substituted Cucurbit[6]uril Bridged β-Cyclodextrin Dimer Mediated Intramolecular FRET Behavior

Abstract: A novel triazolyl bridged cucurbituril (CB)−cyclodextrin (CD) dimer was synthesized via click reaction of monopropargyl modified octamethylcucurbit[6]uril and mono-6-azido-β-cyclodextrin. Moreover, it could form stable supramolecular inclusion complexes possessing efficient fluorescence resonance energy transfer, which benefited from the fact that CD and CB can bind amantadine-and pyridinium-containing fluorophores simultaneously. The supramolecular inclusion complex behaviors were investigated by NMR spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Additionally, taking advantage of the strong binding ability between β-CD and adamantane, 51,52 HA-ADA was introduced into this PET system in aqueous solution to interact with the β-CD unit. Learning from previous reports, 58,59 hyaluronic acid (HA) that possesses excellent aqueous solubility, biocompatibility, and biodegradability can specifically recognize HA receptors (CD44 and RHAMM receptors) over expressed on the tumor cell surface in cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, taking advantage of the strong binding ability between β-CD and adamantane, 51,52 HA-ADA was introduced into this PET system in aqueous solution to interact with the β-CD unit. Learning from previous reports, 58,59 hyaluronic acid (HA) that possesses excellent aqueous solubility, biocompatibility, and biodegradability can specifically recognize HA receptors (CD44 and RHAMM receptors) over expressed on the tumor cell surface in cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a planar triphenylbenzene core bridged β-CD trimer was also synthesized by “click” reaction to investigate the influence of temperature, acidity, and competitive guests on the self-inclusion and dissociation transition . Other kinds of triazolyl bridged cucurbituril (CB)–CD dimer as well as CD–CD and CD–Ad dimers were fabricated to investigate the host–guest interaction-induced self-assembly properties. , …”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] The fascinating macrocyclic compound cucurbiturils (CB[n]), whose skeleton is made up of glycoluril ring moieties, has received a lot of attention. [20][21][22][23][24][25][26][27][28] Bambusurils also have glycoluril as their monomer unit. [29,30] It has been reported that glyoxal and their derivatives can be converted into glycolurils by condensing them with urea using acids like H 2 SO 4 , HCl, H 3 PO 4 , P 2 O 5 and CCl 3 COOH as catalysts.…”
Section: Introductionmentioning
confidence: 99%